Government, Trade, and Comparative Advantage - Clarida, Richard H.; Findlay, Ronald (American Economic Review, 2016)
A country in the theory of international trade is a collection of households endowed with a given supply of productive factors, preferences, and technologies for producing goods that can be traded on world markets. The state plays a rather limited role, usually that of impeding the free flow of goods across national borders with tariffs or other trade restrictions and perhaps transferring income from the winners to losers from international trade. By tradition, the function of the invisible hand of the price system requires little or nothing from an invisible government, which may, for most inquiries, be safely ignored. This tradition, in contrast to many others in economics, does not date back to Adam Smith. Smith regarded governments as performing essential tasks that provide the framework for the efficient operation of private markets. Maintaining law and order, supporting the physical and social infrastructure of the country, and enforcing the contracts that private agents enter into are just several among the many duties of the sovereign without which, according to this Smithian view, a market economy cannot function. While Douglass North (1981) and a few